Confinement and surface effects on the physical properties of rhombohedral-shape hematite (α-Fe2O3) nanocrystals. (August 2016) - Luna, Carlos; Cuan-Guerra, Aída D.; Barriga-Castro, Enrique D.; Núñez, Nuria O.; Mendoza-Reséndez, Raquel
Graphical abstract: Highlights: Uniform rhombohedral hematite nanocrystals (RHNCs) have been obtained. A detailed formation mechanism of these HNCS has been proposed. Phonon confinement effects were revealed in the RHNCS vibrational bands. Quantum confinement effects on the optical and electronic properties were found. Abstract: Morphological, microstructural and vibrational properties of hematite (α-Fe2 O3 ) nanocrystals with a rhombohedral shape and rounded edges, obtained by forced hydrolysis of iron(III) solutions under a fast nucleation, have been investigated in detail as a function of aging time. These studies allowed us to propose a detailed formation mechanism and revealed that these nanocrystals are composed of four {104} side facets, two {110} faces at the edges of the long diagonal of the nanocrystals and two {−441} facets as the top and bottom faces. Also, the presence of nanoscopic pores and fissures was evidenced. The vibrational bands of such nanocrystals were shifted to lower frequencies in comparison with bulk hematite ones as the nanocrystal size was reduced due to phonon confinement effects. Also, the indirect and direct transition band gaps displayed interesting dependences on the aging time arising from quantum confinement and surface effects